Exploring cultural competence in professional development schools - Ferrara, JoAnne, 1955-; Nath, Janice L.; Beebe, Ronald S. (Research in professional development schools., 2020)
"This book examines the ways in which PDSs build cultural competence for various stakeholders including pre-service teachers, classroom teachers, school leaders, college faculty and K-12 students. Given the increased national attention on the opportunity gap present in underserved marginalized communities across the country, the authors in this series identify a combination of research-based practices and institutional changes that increase student attainment and develop educators' capacity to serve a range of diverse learners. We are certain the timeliness of the topic will provide educators with context for understanding the role PDSs play in the creation of culturally responsive schools"--